Pembentukan Karakter Disiplin Mahasantri melalui Kegiatan Keagamaan di Pesantren Tinggi Al-Quds Dewan Dakwah Sumatra Barat - Syahputra, Joni; Muliati, Indah (TSAQOFAH, 2025)
Discipline is a fundamental character trait that shapes a responsible individual, especially amidst the ongoing wave of digitalization and technological advancement. The values of discipline are also embedded in Islamic teachings, as reflected in religious practices such as prayer, fasting, and other devotional activities. This study aims to describe the development of disciplined character among students (mahasantri) through religious activities at Pesantren Tinggi Al-Quds Dewan Dakwah in West Sumatra. A qualitative approach was used, with data collected through observation, interviews, and documentation. The results show that discipline is developed through the routine and structured implementation of religious activities. In congregational prayer, discipline is instilled through understanding the importance of praying in congregation, the formation of a discipline team, the use of a morning wake-up reminder system, and the application of educational sanctions for negligence. In voluntary fasting and group iftar activities, discipline is reinforced through sahur reminders, collective contributions, and sanctions for non-participation. For Islamic study sessions, discipline is fostered through mandatory attendance twice a week, note-taking of the material presented, and sanctions for absenteeism. The conclusion of this study is that consistent and systematic religious activities significantly contribute to the development of discipline among mahasantri. The implication of this study emphasizes the importance of Islamic educational institutions in designing religious programs that are not only ritualistic but also character-building.